The Experiences of Adolescent Pregnancy in Developing Countries - Siti Fatimah; Andari Wuri Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Adolescents are a vulnerable group who need special attention and support during pregnancy. Adolescent pregnancy has physical and phycological impacts such as sexual violence, dropping out of school, the social stigma that exists in the environment so that quality antenatal care services are needed. This study aims to find scientific evidence related to the developmental experience of adolescents in developing countries. This research is a Scoping review using Arkshey and O’Malley Framework and PRISMA-ScR Checklist. The literature search in this study used four databases, namely Pubmed, Wiley Online Library, EBSCO, and Proquest. Grey literature is obtained from search engines, namely Google Scholar and support sites.  The keywords used are adolescent, pregnancy, experience, and scoping review. This study uses the Critical Appraisal Skills Program (CASP) to assess the quality of articles. The first 2,453 articles obtained from the search were then selected into eight articles that were eligible for the next process. The inclusion criteria for the selected articles were articles published from 2016 to 2021, articles from grey literature and related official websites, scientific articles in English and/or Indonesian, and scientific articles that focused on the experiences of adolescents during pregnancy in accessing antenatal care services (ANC), the stigma experienced by adolescent during pregnancy, and partner and family support for adolescents during pregnancy. The selected studies were from seven different countries. The eight eligible articles used a qualitative research design, conducted in the hospitals, clinics, and community settings. The mapping of themes obtained from the results of the analysis of the article is the experience of teenagers during pregnancy in accessing antenatal care services (ANC), the stigma experienced by adolescents, family and partner support for adolescents during pregnancy.  During pregnancy, they need financial, emotional, and psychological support from partners, families, communities, and health workers to obtain quality services, avoid discrimination, stigma, and sexual violence. Abstrak: Remaja merupakan kelompok rentan yang memerlukan perhatian dan dukungan khusus selama masa kehamilan. Kehamilan pada remaja memiliki dampak fisik dan psikis seperti kekerasan seksual, putus sekolah, stigma sosial yang ada di lingkungan sehingga diperlukan pelayanan antenatal yang berkualitas. Penelitian ini bertujuan untuk menggali bukti ilmiah terkait pengalaman kehamilan pada remaja di negara berkembang. Penelitian ini merupakan Scoping review dengan menggunakan Arkshey and O'Malley Framework dan PRISMA-ScR Checklist. Pencarian literatur dalam penelitian ini menggunakan 4 database yaitu Pubmed, Wiley Online Library, EBSCO, dan Proquest. Literatur abu-abu diperoleh dari mesin pencari, yaitu Google Cendekia dan situs pendukung. Kata kunci yang digunakan adalah remaja, kehamilan, pengalaman, dan scoping review. Penelitian ini menggunakan Critical Appraisal Skills Program (CASP) untuk menilai kualitas artikel. 2.453 artikel pertama kali diperoleh dari pencarian yang kemudian diseleksi menjadi 8 artikel yang memenuhi syarat untuk proses review selanjutnya. Kriteria inklusi kriteria artikel terpilih adalah artikel terbitan 2016 hingga 2021, artikel dari grey literature dan website resmi terkait, artikel ilmiah dalam bahasa Inggris dan/Indonesia, dan artikel ilmiah yang berfokus pada pengalaman remaja selama kehamilan dalam mengakses pelayanan antenatal care (ANC), stigma yang dialami remaja saat hamil, dukungan pasangan dan keluarga bagi remaja saat hamil. Penelitian yang dipilih berasal dari 7 negara yang berbeda, 8 artikel yang memenuhi syarat menggunakan desain penelitian kualitatif, dilakukan di rumah sakit, klinik, dan pengaturan komunitas. Pemetaan tema yang diperoleh dari hasil analisis artikel adalah pengalaman remaja selama kehamilan dalam mengakses layanan antenatal care (ANC), stigma yang dialami remaja, dan dukungan keluarga dan pasangan pada remaja selama kehamilan. Selama kehamilan, remaja membutuhkan dukungan finansial, emosional, dan psikologis dari pasangan, keluarga, masyarakat, dan tenaga kesehatan untuk memperoleh pelayanan yang berkualitas, terhindar dari diskriminasi, stigma, dan kekerasan seksual.